2019
DOI: 10.1155/2019/8358954
|View full text |Cite
|
Sign up to set email alerts
|

Arranging Student Scientific Research as an Educational Technology: The Experience of Regional Universities of Russia

Abstract: Nowadays, student scientific research is a significant component for training specialists for Industry 4.0. However, many students do not feel like wanting much to participate in this kind of activity when studying at university. Therefore, there is a challenge in facing educators, i.e., to make a climate of learning in such a way so that learners would not only be able to acquire skills, competences, and proficiencies according to their major but also be able to promote their willingness for independent searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Students' scientific research is an important activity in a university's educational plan (Sadler & McKinney, 2010). Hands-on learning is an effective method for developing students' scientific research capacity (Ruslan I. Bazhenov, 2019;Davidson & Palermo, 2015;Sadler & McKinney, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students' scientific research is an important activity in a university's educational plan (Sadler & McKinney, 2010). Hands-on learning is an effective method for developing students' scientific research capacity (Ruslan I. Bazhenov, 2019;Davidson & Palermo, 2015;Sadler & McKinney, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There have been a number of country specific Edtech platforms that are notable, and in Russia, Skilbox is the Edtech platform with the highest revenue, whereas Stepik, LinguaLeo, and Yandex Praktikum are currently at the forefront of the market. A study has identified that the primary challenges to the adoption of e-learning and Edtech platforms in Russia are inadequate digital infrastructure, insufficient digital literacy skills among educators and learners, and cultural barriers (Bazhenov, 2019). The Edtech industry in China is characterized by intense competition, as established firms and emerging enterprises compete for a slice of the market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Например, в статье Р. Баженова представлены результаты успешного педагогического эксперимента (2014-2018 гг.) по реализации в региональных вузах (Сибири и Дальнего Востока) особой системы научного наставничества [23]. Благодаря ей студенты опубликовали более 450 научных статей, выиграли 28 грантов различного уровня, приняли участие и стали призерами более чем в 50 конкурсах научных исследований.…”
Section: обзор литературыunclassified